Ethical Tenets of PRN Medicines Management in Healthcare Settings: A Clinical Perspective - Mojtaba Vaismoradi; Cathrine Fredriksen Moe; Flores Vizcaya-Moreno; Piret Paal (MDPI AG, 2021)
Prescription and administration of pro re nata (PRN) medications has remained a poorly discussed area of the international literature regarding ethical tenets influencing this type of medication practice. In this commentary, ethical tenets of PRN medicines management from the clinical perspective based on available international literature and published research have been discussed. Three categories were developed by the authors for summarising review findings as follows: 'benefiting the patient', 'making well-informed decision', and 'follow up assessment' as pre-intervention, through-intervention, and post-intervention aspects, respectively. PRN medicines management is mainly intertwined with the ethical tenets of beneficence, nonmaleficence, dignity, autonomy, justice, informed consent, and error disclosure. It is a dynamic process and needs close collaboration between healthcare professionals especially nurses and patients to prevent unethical practice.